Pengaruh Earnings Per Share (EPS) dan Price Earnings Ratio (PER) terhadap Harga Saham Sektor Perdagangan Besar dan Ritel pada Periode 2000-2005 di Bursa Efek Indonesia - Bram Hadianto (Jurnal Akuntansi, 2008)
The aim of this research is to know the impact of earnings per share (EPS) and price earnings ratio (PER) on stock price. Sample of stock that used is taken from wholesaler and retail sector in Indonesian Stock Exchange in 2000-2005 which collected bypurposive sampling method. Regression with panel data is conducted as the method of data analysis. The result states that PER and EPS have positive impact on stock price partially. Simultaneously, PER and EPS have the impact on stock price.Keywords: PER, EPS, stock price